Climate as Related to the Jet Stream in the Orient - Trewartha, Glenn (ERDKUNDE, 1958)
There is fairly convincing evidence that many characteristic features of the climate of East and South Asia result from significant changes in wind systems associated with shifts in jet streams. The highlands of Central Asia play a significant role in these seasonal shifts of jet streams. The fragmentation of the zonal westerly winds during winter, fixing a jet stream of high velocity on the southern flank of the Himalayas, results in important climatic effects. The regenerating and controlling influence of the jet on atmospheric disturbances localizes winter precipitation to northern India- Pakistan and southern China. On the equatorial side of the Himalayan jet, strong downdrafts cause the dry seasons of winter and spring, especially in the subcontinent. The weaker and less locally fixed northern arm of the winter jet, located north of the central highlands, has no such regionalizing effects on winter precipitation as the more fixed southern arm. In the Tibetan lee-side convergence zone between the two winter jets lies one of the main continental regions of strong cyclogenesis, with the disturbances that developed there concentrating winter rains emphatically in southern China. The oceanic centers of cyclogenesis coincide with the winter locations of the two jets near Japan. Simultaneously with the early June shift of the southern jet from its winter position south of the Himalayas to one that passes north of the central highlands, there follows a rapid northward advance of equatorial air over South and East Asia, which in turn ushers in the summer rainy season with the Burst of Monsoon in India and the onset of the Baiu Rains in East Asia